Regioselective Formation of 5-Methylene-6-methoxy-1,4,5,6-tetrahydropyridazines from the [4+2]-Cycloaddition Reaction of In Situ Generated 1,2-Diaza-1,3-dienes with Methoxyallene - Attanasi, Orazio A.; Favi, Gianfranco; Mantellini, Fabio; Mantenuto, Serena; Moscatelli, Giada; Nicolini, Simona (Synlett, 2015)
A regioselective inverse-electron-demand hetero-Diels–Alder reaction of in situ generated 1,2-diaza-1,3-dienes with methoxyallene is reported. These Lewis and Brønsted acid free reactions benefit from operational simplicity and allow access to synthetically valuable 5-methylene-6-methoxy-1,4,5,6-tetrahydropyridazines in high yields.
Keywords: IEDDA; [4+2] cycloaddition; methoxyallene; 1,2-diaza-1,3-dienes; tetrahydropyridazines